Legal Protection Against Victims of Illegal Investment in Purbalingga District (Study in Witness and Victim Protection Institutions) - Pambudi, Tegar Eris (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Illegal investment fraud has become increasingly discussed in the media. Many Indonesians are still unfamiliar with new investment instruments and focus more on potential profits than on proper investment methods. Often, people are only interested in the returns they will receive.This study aims to understand the legal protection for victims of illegal investments in Purbalingga Regency and the obstacles they face. The approach used is a socio-legal approach, which examines the influence of society on the law. The study's findings indicate that victims of illegal investment fraud in Purbalingga are entitled to restitution under Article 7A, paragraph (1) of Law No. 31 of 2014, which amends Law No. 13 of 2006 on the Protection of Witnesses and Victims. This article states that victims of criminal acts are entitled to restitution. However, there are several obstacles to legal protection for victims of illegal investments. Structural obstacles include the large number of victims applying for restitution and the limited human resources at the Witness and Victim Protection Agency (LPSK), causing delays in the application process. Cultural obstacles include the difficulty in organizing victims who apply individually and the fact that many victims do not report their cases to the police, which is necessary for restitution claims. This is due to a lack of understanding among victims about handling illegal investment cases. To date, few victims in Purbalingga have applied for restitution to the LPSK because restitution is only granted upon application.